Planeación tributaria como herramienta estratégica para incrementar la eficiencia en el cumplimiento de obligaciones tributarias en el Hotel Interpacific de Quibdó - Pino Moya, Marlyn; Buenaños Córdoba, Yessica (Universidad Antonio Nariño, 2023)
Today, in Colombia, tax burdens grow every day through tax reforms, which entails adopting planning to comply with obligations as taxpayers, in this way, mitigating the risk of sanctions imposed by the control entity. (DIAN) and take advantage of tax benefits and incentives. The general objective of this work is to carry out tax planning at the Interpacific Hotel in the city of Quibdó, through research into Colombian tax legislation to comply with all obligations. That is why, in this study, it began with the statement of the problem, analyzing the variables of the lack of planning, the risks they run. Then, the objectives are presented, with which it helps to understand tax planning. Next, a theoretical framework and state of the art is presented based on general definitions, historical background, in order to offer greater clarity of the proposal; then, we present the methodology of a descriptive and analytical nature of the tax regulations to comply with the obligations that allow an efficient management of the responsibilities, giving 10 solution to the objectives in the development of the same; Finally, reference is made to the tax calendar to take into account the dates of presentation of the tax.